2013
DOI: 10.1287/orsc.1120.0750
|View full text |Cite
|
Sign up to set email alerts
|

Extending Construal-Level Theory to Distributed Groups: Understanding the Effects of Virtuality

Abstract: Building on prior research on distributed teams that has identified physical and temporal distance as impediments to collaboration and relationship development, this paper explores how and why we treat geographically distant others differently from those who are proximal. According to construal level theory, physically-or temporally-distant events or objects are more psychologically distant and are more likely to be described in terms of their more general characteristics, while views of more proximal events o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 87 publications
(35 reference statements)
2
85
0
1
Order By: Relevance
“…They hypothesized that construal level may predict (a) whether the group views itself as heterogenous or homogenous, (b) whether a given group member is viewed as part of the "in crowd" or as on the margins of the group, (c) whether an individual's negative actions are perceived by the group as being inherent to that person's character or excused on the basis of how they were feeling that day, and (d) whether the perceptions that group members have of each other are inflexible or adaptable. Most relevant for our study, Wilson et al (2013) also indicated aspects of communication in this type of setting that can weaken the usually direct relationship between objective and psychological distance. For example, they suggested that team members who only communicate electronically and never physically meet, may initially "visualize" one another by prototypical/high-level construal.…”
Section: Construal Level Theory: a Theory Of Psychological Distancementioning
confidence: 82%
See 4 more Smart Citations
“…They hypothesized that construal level may predict (a) whether the group views itself as heterogenous or homogenous, (b) whether a given group member is viewed as part of the "in crowd" or as on the margins of the group, (c) whether an individual's negative actions are perceived by the group as being inherent to that person's character or excused on the basis of how they were feeling that day, and (d) whether the perceptions that group members have of each other are inflexible or adaptable. Most relevant for our study, Wilson et al (2013) also indicated aspects of communication in this type of setting that can weaken the usually direct relationship between objective and psychological distance. For example, they suggested that team members who only communicate electronically and never physically meet, may initially "visualize" one another by prototypical/high-level construal.…”
Section: Construal Level Theory: a Theory Of Psychological Distancementioning
confidence: 82%
“…appLiCation oF ConstrUaL LeVeL tHeory to a speCiFiC diGitaL CoMMUniCation ConteXt: soMe eXaMpLes Wilson et al (2013) presented a theoretical analysis of how the perception of psychological distance among members of work teams separated by geographic distance can be understood by applying construal level theory. They offered predictions regarding the effects of objective geographical distance on psychological distance in this kind of work setting, and how this psychological distance in turn will affect group processes.…”
Section: Construal Level Theory: a Theory Of Psychological Distancementioning
confidence: 99%
See 3 more Smart Citations